El control simultaneo y la gestión financiera en la Municipalidad Provincial Datem del Marañon en la región Loreto periodo 2025 - Isuiza Huaymacari, Grey Marycielo (2025)
This study examines the relationship between simultaneous control and financial management in the Provincial Municipality of Datem del Marañón, in the Loreto region, during the year 2024. Using a quantitative, correlational, and non-experimental approach, surveys were applied to a sample of 112 municipal workers, assessing key indicators such as supervision frequency, detection of irregularities, corrective actions, management transparency, and achievement of financial objectives. Through the Spearman's Rho coefficient, a high positive correlation was determined (ρ = 0.882, p < 0.01), confirming that effective supervision significantly impacts the optimization of the municipal budget. The results show that training in internal control and the frequency of audits directly influence employees' satisfaction with financial management (ρ = 0.770, p = 0.0258). Additionally, it was found that implementing immediate corrective actions improves the achievement of economic goals (ρ = 0.685, p = 0.0451). These findings support the need to strengthen real-time oversight and enhance transparency in budget execution. It is recommended to implement digital monitoring mechanisms, train personnel in financial auditing, and establish rapid response protocols for budgetary deviations.